Pros and Cons of Digital Learning - Anneke Warouw (International Journal of Language and Ubiquitous Learning, 2024)
Background. Education in the 21st century has entered the era of the industrial revolution 4.0 so it is required to continue to innovate to digital. The use of digital media in learning does bring benefits, but there are also many problems that arise in addition to these advantages, these problems include changes in low student motivation to be active in learning, decreased interaction between educators and students, saturation in learning and not infrequently academic stress. Purpose. The purpose of this research is to find out the pros and cons of all-digital learning. Method. The method used in this study is a quantitative method, data is obtained through the distribution of questionnaires using google forms. Results. The results of this study show that many students are pro with all-digital learning, but there are also students who are against all-digital learning. This is because some students experience obstacles when doing all-digital learning. This can be seen from students' responses to all-digital learning. Conclusion. The conclusion of this study is important to examine more deeply the pros and cons of digital media-based learning in students.